Enhancing wheat resilience in subtropical agroecosystems through climate-resilient agriculture strategies - Jat, Raj Kumar; Meena, Vijay Singh; Pazhanisamy, S.; Sohane, R.K.; Jha, R.K.; Singh, R.N.; Durgude, Shubham; Kumar, Suneel; Reddy, Illathur R.; Choudhary, Kajod Mal; Meena, Sunita Kumari; Kumar, Brijendu; et al. (Frontiers in Agronomy, 2025)
Wheat production in subtropical agroecosystems is increasingly challenged by climate-induced stresses such as lodging, terminal heat, and erratic rainfall patterns. This study was conducted during the 2023–2024 rabi season across eight locations, namely, the Borlaug Institute for South Asia (BISA) Research Station at Pusa and seven project hubs located in the districts of Munger, Nawada, Nalanda, Katihar, Purnea, Samastipur, and Vaishali in Bihar, India, and evaluated climate-resilient agronomic strategies to enhance wheat resilience and productivity. A randomized block design with 20 replications was used to assess the interactive effects of tillage practices [conventional tillage (CT), zero tillage (ZT), and permanent raised bed (PRB)], sowing times (early vs. timely), and wheat varieties (HD2967, DBW187, and DBW316) on crop performance. Results indicated that PRB and ZT strategies significantly (p < 0.05) reduced (80%–90%) risk of lodging and increased (15%–25%) wheat grain yield compared to CT. Furthermore, early sowing (first fortnight of November) and the use of lodging-resilient varieties of HD2967 and DBW187 reduced crop lodging, improved crop performance, and increased wheat grain yield compared to late sowing (second fortnight of November) and the DBW316 variety, respectively. Correlation and regression analysis studies exposed a weak positive correlation between yield and wind speed (r = 0.133) and a stronger positive correlation effect with rainfall (r = 0.342) during early-sown crops, with stepwise regression indicating yield gains of 0.32 t/ha and 1.15 t/ha under optimum wind speed and rainfall, respectively (r = 0.68). In contrast, late sowing exhibited negative correlations, with yield declining by 0.39 and 0.12 t/ha under aberrant wind and rainfall conditions, respectively (r = 0.52). The study emphasized the significance of adopting climate-resilient agronomic strategies, such as ZT, appropriate variety selection (HD2967 and DBW187), and early sowing, to enhance the sustainability and resilience of wheat production under adverse climatic conditions.